2013
DOI: 10.1111/scd.12022
|View full text |Cite
|
Sign up to set email alerts
|

Behavior guidance techniques in Pediatric Dentistry: attitudes of parents of children with disabilities and without disabilities

Abstract: This study compared the parental acceptance of pediatric behavior guidance techniques (BGT). Forty parents of children without disabilities (Group A) and another 40 parents of children with disabilities (Group B) were selected. Each BGT was explained by a single examiner and it was presented together with a photograph album. After that parents evaluated the acceptance in: totally unacceptable, somewhat acceptable, acceptable, and totally acceptable. Results indicated that in Group A, the BGT based on communica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 4 publications
1
9
0
6
Order By: Relevance
“…This may affect treatment decisions, potentially increasing the use of techniques such as ART, or more negatively increasing the incidence of extractions. There is reason to believe that the factors influencing the final decision to refer to DGA or to sedation are multiple and that these factors act on different levels, not specifically captured by this study: the socioeconomic status of the children's family, immigrant background, dental anxiety, parents' and dental professionals' attitudes to sedation, availability of specialist dental clinics, and national organisation of oral disease prevention being a few such factors 9,[29][30][31][32][33] . Most of these may be at least partly compensated by a well-organised and well-financed dental health service.…”
Section: Discussionmentioning
confidence: 99%
“…This may affect treatment decisions, potentially increasing the use of techniques such as ART, or more negatively increasing the incidence of extractions. There is reason to believe that the factors influencing the final decision to refer to DGA or to sedation are multiple and that these factors act on different levels, not specifically captured by this study: the socioeconomic status of the children's family, immigrant background, dental anxiety, parents' and dental professionals' attitudes to sedation, availability of specialist dental clinics, and national organisation of oral disease prevention being a few such factors 9,[29][30][31][32][33] . Most of these may be at least partly compensated by a well-organised and well-financed dental health service.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been attempted to investigate the attitude of parents toward BMTs. 10,14,21 Those studies concluded that most of the parents prefer to accompany their children in the dental operatory. 14,21 A dentist should understand that some parents would not agree on being separated from their children as they feel that they should protect them in the dental clinic.…”
Section: Discussionmentioning
confidence: 99%
“…10 Advanced BMTs include protective restraint, sedation, and general anesthesia, which require informed consent from the parents or legal guardian. 10 The BMTs should be learned and developed by all staff in the pediatric dental clinic, starting with the receptionist, who welcomes the parents and their child and ending with the pediatric dentist, who will perform the treatment. 6,7 Parental presence/absence is one of the nonpharmacological BMTs.…”
Section: 5005/jp-journals-10024-2243mentioning
confidence: 99%
“…Seven studies evaluated the parents of SHCN children. The children were medically or physically compromised with neuropathological disorders 15 , with intellectual disabilities 16 , with physical or mental disabilities 17 , with physical or congenital disabilities, with mental, intelligence or behavioral deviations and/or systemic chronic diseases 18 with a range of disabilities including Down's Syndrome and cerebral palsy 19 . They also may have had autism 20 , and a cleft lip and/or palate 21 (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%